Electron beam refining in production of platinum and platinum-base alloys. Information 1. Electron beam refining of platinum - Savenko, V.A.; Grechanyuk, N.I.; Churakov, O.V. (Современная электрометаллургия, 2008)
Commercial technology for production of platinum in ingots with content of the base element not less than 99.99 % was developed. Разработана промышленная технология получения платины в слитках с содержанием основного элемента не менее 99,99 %.